2020
DOI: 10.1186/s13052-020-00838-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns and associated risk factors of congenital malformations in twins

Abstract: Background: The rate of twinning continues to increase due to the combined effect of a rise in parental age and increased use of assisted reproductive technology. The risk of congenital anomalies in twins is higher than in singletons, but it is less well reported in relation to growth patterns. We focused to the auxological outcome of twin pregnancies when one or both of twins are affected by one or more malformations. Methods: We conducted a retrospective observational study reviewing the clinical charts of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…19 Monozygotic twinning is associated with early embryonic midline structural defects such as ventral body wall defects, holoprosencephaly malformation sequence, exstrophy of the cloaca malformation sequence, the VATERR association, and sirenomelia. 20 Only 5%-20% of such cases are concordant. 10,21 This seems to be the case for ectopia cordis as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Monozygotic twinning is associated with early embryonic midline structural defects such as ventral body wall defects, holoprosencephaly malformation sequence, exstrophy of the cloaca malformation sequence, the VATERR association, and sirenomelia. 20 Only 5%-20% of such cases are concordant. 10,21 This seems to be the case for ectopia cordis as well.…”
Section: Resultsmentioning
confidence: 99%
“…The mean maternal age was 27.7 (range 19-33) years, the mean gestational week at diagnosis was 14.8 ± 6.5 (median: 12, range [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] weeks. Six of the eight cases were diagnosed in the first trimester, one fetus in the second trimester, one fetus was identified in the third trimester.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piro et al (22) found the frequency of congenital anomalies in twin pregnancies as 11%. We found this rate lower in our patient population (3.5%).…”
Section: Discussionmentioning
confidence: 98%
“…Infant birth sizes, including body weight, crown–heel length, and head circumference at birth, are widely used to evaluate intrauterine growth and nutrition status [ 7 ]. Low birth weight after abnormal fetal growth is of prognostic significance for predicting perinatal death, congenital malformations, or nervous system abnormalities in early life [ 8 , 9 , 10 ]. Notably, infant sizes at birth have a linear relation with the amount of iron stores during the first 6–8 months of life [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%